Evaluation of Changes in Per Capita Green Space in Sulaimani City (مجلة ديالى للبحوث الانسانية, 2022)
In this current study, evaluation of changes in per capita of green space this study explains  (2007-2016) in Sulaimani City and results compared with international standards. The lowest per capita was 9.2m2 in 2008, and the highest per capita was 16.2m2 in 2016. Currently, the total green space in Sulaimani city is 10%. Despite the green space is lower than the standards, its distribution tends to be various among different parts of the city. In some of the bigger parts of the city, the area of green space is considerably low and the population is high. Also, in the new areas of the city, the planned parks are not completed, and even if they are completed, their areas are smaller compared to the population size which is steadly increasing. The planned parks should be completed until the green spaces will increase in a reasonable percentage in Sulaimani City in the future